Crustal Structure Across the Lord Howe Rise, Northern Zealandia, and Rifting of the Eastern Gondwana Margin. Issue 3 (4th March 2019) - Gallais, Flora; Fujie, Gou; Boston, Brian; Hackney, Ron; Kodaira, Shuichi; Miura, Seiichi; Nakamura, Yasuyuki; Kaiho, Yuka
Abstract: During the Late Cretaceous, the fragmentation of eastern Gondwana led to the formation of the narrow eastern Australian margin and the wide Lord Howe Rise during the opening of the oceanic Tasman Basin. To provide crustal‐scale constraints on this margin, a 680‐km‐long, east‐west oriented refraction transect with 100 ocean bottom seismometers was acquired from the Tasman Basin to the Lord Howe Rise. After traveltime tomographic inversion of the first refracted arrivals and reflected arrivals from the Moho, the final P wave velocity model reveals strong variations in crustal thickness. The Tasman Basin is floored by a two‐layered and 7‐km‐thick oceanic crust. To the east, the Middleton Basin separates the Dampier Ridge, with 16‐km‐thick continental crust, from the Lord Howe Rise, where the extended continental crust is 20–23 km thick. Below the Middleton Basin, Moho reflections are recorded at the base of 7‐km‐thick crust. The velocity gradient of this two‐layer crust suggests an oceanic origin for the Middleton Basin. Our results show no clear evidence for mantle exhumation or a sizable igneous intrusion within three separate and relatively narrow (<70 km) necking zones. The northwestern Zealandia margin thus appears to be magma poor and, despite the considerable width of this margin (>1, 000 km), the lack of evidence for mantle exhumation, the evidence for oceanic crust under the Middleton Basin, and the narrow necking zones combine to suggest that northern Zealandia is not a hyperextended margin. Key Points: The Lord Howe Rise and Dampier Ridge are thinned Zealandia continental fragments separated by oceanic crust in the Middleton Basin There is no evidence for mantle exhumation or high‐velocity igneous intrusive bodies during rifting and breakup of eastern Gondwana Despite the width and magma‐poor nature of northwestern Zealandia, it lacks other typical features of a hyperextended continental margin